A note on preconditioner for the Ohta–Kawasaki equation. (November 2018) - Li, Rui-Xia; Liang, Zhao-Zheng; Zhang, Guo-Feng; Liao, Li-Dan; Zhang, Lei
Abstract: In this paper, an efficient preconditioner is proposed for the discrete Ohta–Kawasaki system. We show that the eigenvalues of the new preconditioned matrix are the same as that of the recently published block triangular preconditioner in [P. E. Farrell, J. W. Pearson, SIAM J. Matrix Anal. Appl. 38(1) (2017) 217–225]. Numerical experiments are presented to illustrate the effectiveness and feasibility of the new preconditioner to accelerate GMRES method.